Conflict-Induced Displacement of Skilled Refugees: A Cross-Case Analysis of Syrian Professionals in Selected OECD Countries - Camelia Tigau (Norteamérica)
The mainstream literature on skilled diasporas has focused on economically-induced professional migration and free-choice mobility of educational elites. I introduce the concept of conflict-induced displacement of skilled refugees (CIDSR) to study the skilled Syrian refugees as political migrants who flee from violence and conflict in their home countries. I use a cross-case analysis of seven OECD countries (Brazil, Canada, Germany, Mexico, Turkey, the U.K. and the U.S.) to prove that the Syrian CIDSR is a crisis but also an economic and political opportunity. OECD countries take advantage of the skilled refugees in order to maintain growth in their aging economies, solve brain drain caused by internal conflict, as well as to strengthen their status as moral powers.